Taxonomic revalidation and potential distribution of Armatocereus brevispinus Madsen (Cactaceae) - Loaiza S., Christian R. (2016)
We report the first confirmed record for northern Peru of Armatocereus brevispinus Madsen, a species of cactus regarded as endemic to the province of Loja, in the southern region of Ecuador. The record corresponds to a locality placed near the km 18 of the route to Ayabaca (04º42’21.0”S and 79º48’51.0”W), in the district of Ayabaca, within the province of Ayabaca, in the Department of Piura. This records represents an extension of the distributional range known for this species in Ecuador. We analyze its taxonomy and the distribution and conservation status and comments on its biogeography in the Andean region.